Parameters for Optoperforation-Induced Killing of Cancer Cells Using Gold Nanoparticles Functionalized With the C-terminal Fragment of Clostridium Perfringens Enterotoxin - Becker, Annegret (Int J Mol Sci, 2019)
Recently, we used a recombinant produced C-terminus (D194-F319) of the Clostridium perfringens enterotoxin (C-CPE) to functionalize gold nanoparticles (AuNPs) for a subsequent specific killing of claudin expressing tumor cells using the gold nanoparticle-mediated laser perforation (GNOME-LP) technique. For a future in vivo application, it will be crucial to know the physical parameters and the biological mechanisms inducing cell death for a rational adaptation of the system to real time situation. Regarding the AuNP functionalization, we observed that a relationship of 2.5 × 10(−11) AuNP/mL to 20 µg/mL C-CPE maximized the killing efficiency. Regardingphysical parameters, a laser fluence up to 30 mJ/cm(2) increased the killing efficiency. Independent from the applied laser fluence, the maximal killing efficiency was achieved at a scanning velocity of 5 mm/s. In 3D matrigel culture system, the GNOME-LP/C-CPE-AuNP completely destroyed spheroids composed of Caco-2 cells and reduced OE-33 cell spheroid formation. At the biology level, GNOME-LP/C-CPE-AuNP-treated cells bound annexin V and showed reduced mitochondria activity. However, an increased caspase-3/7 activity in the cells was not found. Similarly, DNA analysis revealed no apoptosis-related DNA ladder. The results suggest that the GNOME-LP/C-CPE-AuNP treatment induced necrotic than apoptotic reaction in tumor cells.